The Optimization Design of the Accurate Community Navigation Map for the Terminal Distribution to Promote the Development of E-Commerce New Retail - Lijin Liu (Journal of Advanced Transportation)
In recent years, the development of e-commerce new retail formats is in full swing, and the terminal distribution has become a hot research topic under the background of new retail. The accuracy of the community navigation map is related to the low cost and high efficiency of terminal distribution and then affects the development of new e-commerce retail. However, in large communities, the existing navigation map software can only locate the main entrance of the community, and there is a lack of effective positioning for the location of buildings. Therefore, based on the existing navigation map, this paper expects to correct its application defects and carry out optimization design from the design principle, design idea, product function, product customization, and product application effect, so as to make the community navigation more accurate, faster, and more efficient, to help the low cost and efficient development of door-to-door distribution under the new retail of e-commerce.